Ek yatra, anupreksha aur Karuna ki [A journey of care and compassion] - Rajput, Vijay (Research and Humanities in Medical Education, 2020)
This artwork - the face of the global healthcare worker before and after COVID-19 - was created as a tribute to all the healthcare workers on frontlines everywhere in the world. For your selfless helping of patients and the community of global villages during the COVID-19 Pandemic, I offer my gratitude and respect. "If I can stop one heart from breaking, I shall not live in vain: if I can ease one life the aching, Or cool one pain, Or help one fainting robin Unto his nest again, I shall not live in vain." by Emily Dickenson; 'Not in Vain' From One Hundred and One Famous Poems: with a Prose Supplement - An Anthology. Cook RJ (Editor). Chicago: The Cable Company, 1929.